264 Field Test of Sound Machine Shows Significant Improvement in Perceived Sleep but Not Objective Sleep. (3rd May 2021) - Danoff-Burg, Sharon; Rus, Holly; Rodriguez, Rodolfo; Weaver, Morgan; Raymann, Roy
Abstract: Introduction: Ambient sound can mask external environmental noise, reducing sleep disturbances. Recently there has been a call for research with objective sleep measures examining noise as a sleep aid. This study investigated whether using a sound machine (Sound+Sleep SE) would improve sleep in healthy adults whose objective sleep data indicated difficulty falling asleep or waking up frequently during the night. In-home field testing provides insight into the effectiveness of sleep products under real-life conditions, yielding more ecologically valid results. Methods: A within-subjects, pre-post intervention design was implemented, comparing a 2-week baseline period to 2 weeks of nightly product use. Participants (n=30) measured their sleep nightly using SleepScore by ResMed technology. Sleep experience questionnaires were completed before and after product use. Participants were instructed to use their preferred settings and sound options for the duration of the product use period and to refrain from using other types of sounds for sleep. Multilevel regression and paired t-tests were used to test for statistical significance. Results: Across participants (63% male; age 28-72, avg. 53), there were 725 nights of tracked sleep. Multilevel analyses revealed no significant differences in objectively-measured sleep outcomes. However, improvements were seen in many aspects of self-reported sleep while using the sound machine: 30% decrease in perceived minutes to fall asleep (p<.05); 76% increase in perceived ability to sleep through the night (p<.001); 37% increase in perceived sleep quality (p<.01); and 46% increase in feeling rested upon waking in the morning (p<.001). Additionally, at the beginning of the study, 60% of participants reported having racing thoughts or worrying when trying to fall asleep. While using the sound machine, only 30% of participants experienced this concern. Conclusion: Participants perceived a variety of benefits from sound machine use, even though these improvements were not observed in their objective sleep data. Given that adjustment to any product used during sleep varies from person to person, it is possible that changes in the objective sleep data might have been observed if the product use period had been longer. This study adds to the ongoing discussion of using noise as a sleep aid. Support (if any): ASTI